2021
DOI: 10.19101/ijatee.2020.762139
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence application for predicting slope stability on soft ground: a comparative study

Abstract: This paper aimed to estimate the slope stability on soft ground by utilising Artificial Intelligence (AI) method that is widely used in the past decade for prediction purposes. The slope stability is predicted using Factor of Safety (FoS) that is generated with Limit Equilibrium Method (LEM) such as Ordinary, Bishop, Janbu and Morgenstern-Price and the total of 233 random datasets in this study. The output of the FoS is also estimated using the input parameters of height of slope (H), unit weight slope aterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In this analysis, ANFIS has been the most popular and successful neuro-fuzzy system used in diverse applications and different research domains, including business, medicine, IS, construction, and engineering. Omar et al (2021) compared ANFIS and ANN model accuracies using the RMSE value to forecast the slope stability on soft ground, and it was found that the former model RMSE was higher than the latter RMSE. In that sense, a big data mining-based paddy leaves monitoring system model elaborated on five phases: image acquisition, segmentation, feature extraction, feature selection, and ANFIS classification, showed improved accuracy of 97.28 percent compared to other models accuracies (SVM classifier: 91.2%, KNN: 85.3% and ANN: 88.78%) (Suresh et al, 2020).…”
Section: Neuro-fuzzy Modelsmentioning
confidence: 99%
“…In this analysis, ANFIS has been the most popular and successful neuro-fuzzy system used in diverse applications and different research domains, including business, medicine, IS, construction, and engineering. Omar et al (2021) compared ANFIS and ANN model accuracies using the RMSE value to forecast the slope stability on soft ground, and it was found that the former model RMSE was higher than the latter RMSE. In that sense, a big data mining-based paddy leaves monitoring system model elaborated on five phases: image acquisition, segmentation, feature extraction, feature selection, and ANFIS classification, showed improved accuracy of 97.28 percent compared to other models accuracies (SVM classifier: 91.2%, KNN: 85.3% and ANN: 88.78%) (Suresh et al, 2020).…”
Section: Neuro-fuzzy Modelsmentioning
confidence: 99%
“…In some cases, the application of deep learning techniques in more traditional scientific disciplines can unlock unseen capabilities (e.g., control theory in geomechanics [ 13 ]). In other cases, deep learning has been limited to fitting problems, e.g., in the prediction of pile bearing capacity [ 14 ], slope staility [ 15 ], or rupture distances and capillary forces in wet granular media [ 16 ]. Fitting problems can be enriched with physics and thermodynamics supervision as well [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using artificial intelligence techniques, it is possible to determine the relationship between different parameters with a high degree of accuracy, without prior knowledge. Various topics in geotechnical engineering, such as slope stability [25][26][27], tunneling [28][29][30], pavement and road construction [31,32], soil cracking [33][34][35], rock mechanics [36,37], soil dynamics [38][39][40][41], and soil stabilizers [42][43][44] have been addressed using artificial intelligence methods [45]. Nevertheless, only two studies have used artificial intelligence to predict the properties arising from mixing sludge with soil [46,47].…”
Section: Introductionmentioning
confidence: 99%